Sphingosylphosphorylcholine inhibits plasma cell differentiation and ameliorates experimental autoimmune encephalomyelitis - Park, Byunghyun; Jeong, Yu Sun; Hu, Wonseok; Lee, Mingyu; Kim, Ji Cheol; Bae, Geon Ho; Bae, Yong-Soo; Bae, Yoe-Sik (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is a potentially disabling disease that damages the brain and spinal cord, inducing paralysis of the body. While MS has been known as a T-cell mediated disease, recent attention has been drawn to the involvement of B cells in its pathogenesis. Autoantibodies produced by B cells have a strong association with the development of central nervous system damage and can contribute to a poorer prognosis. Therefore, regulating the activity of antibody secreting cell could be related with the severity of the MS symptoms. In this study, we found that plasma cell differentiation was accompanied by upregulation of autotaxin, which converts sphingosylphosphorylcholine (SPC) to sphingosine 1-phosphate in response to LPS. We observed that SPC strongly blocked plasma cell differentiation from B cells and antibody production in vitro. SPC downregulated LPS-stimulated IRF4 and Blimp 1, which are required for the generation of plasma cells. SPC-induced inhibitory effects on plasma cell differentiation were specifically blocked by VPC23019 (S1PR1/3 antagonist) or TY52156 (S1PR3 antagonist), but not by W146 (S1PR1 antagonist) and JTE013 (S1PR2 antagonist), suggesting a crucial role of S1PR3 but not S1PR1/2 in the process. Administration of SPC against an experimental autoimmune encephalomyelitis (EAE) mouse model significantly attenuated the symptoms of disease, showing decreased demyelinated areas of the spinal cord and decreased numbers of cells infiltrated into the spinal cord. SPC markedly decreased plasma cell generation in the EAE model, and SPC-induced therapeutic effects against EAE were not observed in μMT mice. Collectively, we show that SPC inhibits plasma cell differentiation and elicits therapeutic outcomes against EAE, an experimental model of MS, suggesting SPC as a new material to control MS.